Effects of Adjacent Vehicles on Judgments of a Lead Car During Car Following. (November 2016) - Levulis, Samuel J.; DeLucia, Patricia R.; Oberfeld, Daniel
Objective: Two experiments were conducted to determine whether detection of the onset of a lead car's deceleration and judgments of its time to contact (TTC) were affected by the presence of vehicles in lanes adjacent to the lead car. Background: In a previous study, TTC judgments of an approaching object by a stationary observer were influenced by an adjacent task-irrelevant approaching object. The implication is that vehicles in lanes adjacent to a lead car could influence a driver's ability to detect the lead car's deceleration and to make judgments of its TTC. Method: Displays simulated car-following scenes in which two vehicles in adjacent lanes were either present or absent. Participants were instructed to respond as soon as the lead car decelerated (Experiment 1) or when they thought their car would hit the decelerating lead car (Experiment 2). Results: The presence of adjacent vehicles did not affect response time to detect deceleration of a lead car but did affect the signal detection theory measure of sensitivity d ′ and the number of missed deceleration events. Judgments of the lead car's TTC were shorter when adjacent vehicles were present and decelerated early than when adjacent vehicles were absent. Conclusion: The presence of vehicles in nearby lanes can affect a driver's ability to detect a lead car's deceleration and to make subsequent judgments of its TTC. Application: Results suggest that nearby traffic can affect a driver's ability to accurately judge a lead car's motion in situations that pose risk for rear-end collisions.